Interleukin-2-Inducible T-Cell Kinase Deficiency—New Patients, New Insight? - Ghosh, Sujal; Drexler, Ingo; Bhatia, Sanil; Adler, Heiko; Gennery, Andrew R.; Borkhardt, Arndt (Frontiers in Immunology, 2018)
Patients with primary immunodeficiency can be prone to severe Epstein-Barr virus (EBV) associated immune dysregulation. Individuals with mutations in the Interleukin-2 inducible T-cell kinase (ITK) gene experience Hodgkin and Non-Hodgkin lymphoma, EBV lymphoproliferative disease, hemophagocytic lymphohistiocytosis and dysgammaglobulinemia. In this review we give an update on further reported patients. We believe that current clinical data advocate early definitive treatment by hematopoietic stem cell transplantation, as transplant outcome in primary immunodeficiency disorders in general has gradually improved in recent years. Furthermore, we summarize experimental data in the murine model to provide further insight of pathophysiology in ITK deficiency.